2020
DOI: 10.5194/acp-2019-1041
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of continental emissions on Cloud Condensation Nuclei (CCN) activity in northern South China Sea during summertime 2018

Abstract: <p><strong>Abstract.</strong> Aerosol particles in marine atmosphere have been shown to significantly affect cloud formation, atmospheric optical properties, and climate change. However, high temporal and spatial resolved atmospheric measurements over sea are currently sparse, limiting our understanding of aerosol properties in marine atmosphere. In this study, a ship-based cruise campaign was conducted over northern South China Sea (SCS) region (19°37&… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…113º44'E to 118º12'E) in August 2018 (Cai et al, 2020), and no obvious dependence of κa on particle size (50-100 nm) was observed. The campaign-averaged κ was determined to be ~0.40 (Cai et al, 2020), larger than these measured in the PRD region but smaller than those measured over remote marine regions. This is because the air in north South China Sea was affected by both continental air masses (low hygroscopicity) and marine background (high hygroscopicity).…”
Section: Other Locationsmentioning
confidence: 85%
See 4 more Smart Citations
“…113º44'E to 118º12'E) in August 2018 (Cai et al, 2020), and no obvious dependence of κa on particle size (50-100 nm) was observed. The campaign-averaged κ was determined to be ~0.40 (Cai et al, 2020), larger than these measured in the PRD region but smaller than those measured over remote marine regions. This is because the air in north South China Sea was affected by both continental air masses (low hygroscopicity) and marine background (high hygroscopicity).…”
Section: Other Locationsmentioning
confidence: 85%
“…Bimodal hygroscopicity distributions were observed for 40-200 nm particles, and the average κ increased with particle size, from 0.213 at 40 nm to 0.312 at 200 nm. The κ values derived from size-resolved chemical compositions measured using AMS were significantly lower than those derived from GF measurements (Cai et al, 2017;Cai et al, 2018), probably because using a constant κ value (0.1) may underestimate hygroscopicity of aerosol organics. Aerosol composition and hygroscopic growth at 90% RH were investigated at this site in September-October (Hong et al, 2018), using an ACSM and a H-TDMA.…”
Section: Urban/suburban Sites In Guangzhoumentioning
confidence: 89%
See 3 more Smart Citations